Evaluation of flavored mono-sodium glutamate in swine starter rations - G L Allee; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1972)
Suckling pigs (2 to 4 weeks old) offered a choice of diets containing either flavored or unflavored mono-sodium glutamate (F-MSG or MSG) consumed 3.5 times more of the flavored than of the unflavored diet. Likewise, litters of suckling pigs offered only F-MSG diets consumed 3.5 times more than litters offered only the MSG diet. After weaning, pigs with access to F-MSG during the pre-weaning phase exhibited an initial and continued preference for the F-MSG diet by consuming 3.8 times more of it than of the MSG diet in preference trials. Pre-weaning feeding of pigs altered initial post-weaned preference patterns, as pigs with access to only the MSG diet did not prefer the F-MSG ration until the second week of the preference trial. In the second experiment, weaned pigs fed a flavored starter diet (flavor only) consumed significantly more feed per day and gained significantly faster than pigs fed either the F-MSG or MSG diets used in experiment I. Pigs fed the flavored ration consumed more feed per day than pigs fed the unflavored ration, but not significantly more. The feed:gain ratio of all treatments; flavor, F-MSG, MSG, and basal diet were similar.; Swine Day, Manhattan, KS, November 2, 1972
Keywords: Swine day; 1972; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 193; Swine; Flavored mono-sodium glutamate; Starter rations; Feed/gain ratio